2017
DOI: 10.2147/opth.s133775
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative changes of the intraocular pressure during the treatment of epiretinal membrane by using 25- or 27-gauge sutureless vitrectomy without gas tamponade

Abstract: PurposeThe purpose of this study was to compare perioperative intraocular pressures (IOPs) in 25- or 27-gauge microincision vitrectomy surgery (MIVS) and to evaluate the stability of postoperative sclerotomy closure.Materials and methodsThis is a retrospective review of 147 eyes treated for epiretinal membrane by using 25- or 27-gauge MIVS as the initial vitrectomy (25-gauge phacovitrectomy [25-P group]: 73 eyes, 25-gauge vitrectomy alone [25-A group]: 15 eyes, 27-gauge phacovitrectomy [27-P group]: 47 eyes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…In consequence, shorter scleral tunnel could be created with higher possibility of wound leakage and prolonged healing. It is difficult to compare our result with the ones obtained by Naruse et al [8] and Nakashina et al [10] because of different angle of trocar placement, use of air or gas exchange, phacovitrectomy performance and more than one operating surgeon involved.…”
Section: Complicationsmentioning
confidence: 54%
See 1 more Smart Citation
“…In consequence, shorter scleral tunnel could be created with higher possibility of wound leakage and prolonged healing. It is difficult to compare our result with the ones obtained by Naruse et al [8] and Nakashina et al [10] because of different angle of trocar placement, use of air or gas exchange, phacovitrectomy performance and more than one operating surgeon involved.…”
Section: Complicationsmentioning
confidence: 54%
“…The use of 27G PPV in the treatment for posterior segment diseases [4][5][6] becomes more and more common, including the surgical treatment of some macular diseases, such as epiretinal membranes. There are no conclusive study results in the literature available that would indicate superiority of 27G vitrectomy over 25G vitrectomy in the treatment for epiretinal membranes [7][8][9][10]. That is why we decided to conduct this prospective study on 60 eyes with idiopathic epiretinal membranes undergoing 27G or 25G vitrectomy and compare postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore the potential sources of heterogeneity, sensitivity analysis (via excluding the studies one by one) was proceeded. After the Takashina et al study [17] was excluded, the heterogeneity almost disappeared (I 2 � 19%, P � 0.27; MD � 3.64; 95% CI: 2.29, 4.99; P < 0.001), which indicated this study can be identified as the main contributor of heterogeneity. We reevaluated the study of Takashina et al in terms of design, statistics, and selection bias and did not find anything wrong.…”
Section: Operation Timementioning
confidence: 83%
“…Seven studies [ 15 , 21 24 , 26 , 31 ] were designed as prospective randomized/nonrandomized comparative study and four studies [ 17 , 25 , 29 , 30 ] were retrospective randomized/nonrandomized comparative study. Five trials [ 15 , 17 , 21 , 24 , 29 ] enrolled 554 eyes which were conducted on ERM and six studies [ 22 , 23 , 25 , 26 , 30 , 31 ] enrolled 386 eyes which were conducted on RRD. In total, 940 eyes were included in this meta-analysis; 439 eyes were assigned to the 27-G vitrectomy group and 501 eyes to the 25-G group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation